TRANSFORMASI DIGITAL DAN ADOPSI ARTIFICIAL INTELLIGENCE DALAM PRAKTIK AUDIT LAPORAN KEUANGAN: SEBUAH SYSTEMATIC LITERATURE REVIEW - Muhammad Prans Panca Renta; Nurul Syahbela; Amirul Bahar (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2025)
Indonesian-language abstracts were written using Times New Roman-10. Spacing between lines 1 space. Abstracts contain 150-250 words and consist of a maximum of 1 paragraph, which contains background and purpose (is the core of the preliminary explanation), research methods, and research results. The development of digital transformation and the application of Artificial Intelligence (AI) have shifted the paradigm of financial statement audits toward a more intelligent and data-driven system. However, the level of readiness of the auditor profession and the effectiveness of its implementation still vary across contexts. This study seeks to delineate research trends concerning AI in digital audits from 2020 to 2025, evaluate the methodologies and principal findings of current studies, and formulate a conceptual framework for future research trajectories. The method used is a Systematic Literature Review (SLR) based on 13 relevant international journal articles, accompanied by bibliometric analysis using VOSviewer software to map themes and relationships between research topics. The results show that research on AI-based audits has evolved from a conceptual approach to empirical analysis that assesses the impact of technology on audit quality, efficiency, and organizational governance. Three key dimensions that determine the success of digital audits are technology, human competency, and organizational governance, which are then integrated in the Digital–AI–Audit Integration Framework (DAA-IF) conceptual model. This study provides a theoretical contribution by outlining the research development map and offering new research directions to strengthen audit governance in the era of artificial intelligence.